Pengaruh Konsentrasi Pupuk Kalium Boron dan Mikro terhadap Produksi Kedelai (Glycine max (L.) Merril) - Iqbalullah, Mujib; Sri Wahyuni, Endang (Program Studi Agroteknologi, 2022)
One of the effort to increase soybean production can be done with fertilization. Effect of fertilizer to the land is to create a high level of nutrients and can improve the quality of the crop. Fertilization through leaves intended that nutrients can be absorbed quickly by plants. Macro elements such as potassium (K) and micronutrients such as boron (B) and other micro elements are needed on soybeans. The research objective was to determine the effect of concentration of Boron and Potassium Fertilizer on Soybean Production Micro (Glycine max L. Merrill). This research was conducted in paddy fields in August up to November 2016, in the village Kertonegoro, district Jenggawah Jember district. The study was conducted using a Randomized Block Design (RBD) consisted of two factors with three replications. The first factor is the concentration of potassium boron (KB) consists of 0 ml/l (KB0), 1.5 ml/l (KB1), 3 ml/l (KB2) and the second factor is the concentration of micro fertilizer (M) consisting of 0 g/l (M0), 0.125 g/l (M1), 0.25 g/l (M2). The results showed that fertilizer treatments of Potassium Boron influence on the parameters of a number of branches, number of pods and pod weight, but has no effect on the parameters plant height and number of leaves per plant soybeans. KB2 (3 ml/l) gives the highest production. Micro fertilizer treatment effect on the parameters pod number and weight of pods, but has no effect on the parameters plant height, number of leaves and number of branches. m2 (0,25 g/l) gave the highest soybean production. Potassium fertilizer combination treatment Micro Boron and give effect to the parameter number of pods and pod weight, but the effect on the parameters plant height, number of leaves and number of branches. The highest soybean production in KB2M1 treatment (potassium boron 3 ml/l and micro 0,125 g/l) which is 38.33 grams per plant.